Salivary peptidomic profiling of chronic gingivostomatitis in cats by matrix‐assisted laser desorption/ionization‐time‐of‐flight mass spectrometry and nanoscale liquid chromatography‐tandem mass spectrometry - Sekkarin Ploypetch; Apisit Pornthummawat; Sittiruk Roytrakul; Janthima Jaresitthikunchai; Narumon Phaonakrop; Sabrina Wahyu Wardhani; Sitthichok Lacharoje; Somporn Techangamsuwan (Journal of Veterinary Internal Medicine)
Abstract Background Chronic gingivostomatitis in cats (FCGS) is a moderately to severely painful condition, potentially caused by inadequate immune response to oral antigenic stimulation. Salivary peptidome analysis can identify inflammatory protein mediators and pathways involved in oral mucosal immune activation and may indicate potential therapeutic options for FCGS. Objective Evaluate the diversity and abundance of salivary peptides in cats with FCGS using matrix‐assisted laser desorption/ionization‐time‐of‐flight mass spectrometry (MALDI‐TOF MS) and nanoscale liquid chromatography‐tandem mass spectrometry (nano LC‐MS/MS). Animals Thirty‐two cats with FCGS and 18 healthy controls. Methods Case‐control cross‐sectional study. We compared the salivary peptide profiles of diseased and healthy cats. The diagnosis of FCGS was confirmed by histopathology. Saliva samples were analyzed for viral infections using polymerase chain reaction (PCR), peptide mass fingerprint (PMF) using MALDI‐TOF MS, and peptide identification using nano LC‐MS/MS. Results Distinct clusters of peptide profiles were observed between groups. In FCGS, 26 salivary peptides were altered, including apolipoprotein A1, nuclear receptor subfamily 1 group I member 3, fibrinogen alpha chain, interleukin 2 receptor gamma, interleukin 23 receptor, hemoglobin subunit alpha, and serpin peptidase inhibitor clade A (alpha‐1 antiproteinase, antitrypsin) member 12, protein‐tyrosine‐phosphatase, and cholinergic receptor nicotinic alpha 10 subunit. Protein‐anti‐inflammatory drug interaction networks were observed. Conclusions and Clinical Importance Peptide mass fingerprint and peptide profiles identified distinct clusters between FCGS and healthy cats. The 9 novel salivary peptide markers were associated with the JAK/STAT and PI3K/Akt pathways and immune responses. These potentially noninvasive biomarkers may facilitate understanding of FCGS pathophysiology and guide future therapeutic research.